Pembentukan Kompetensi Calon Pelaut Dalam Kepemimpinan Kelompok Kerja Abk Dek Muka Dengan Model Role Play - Ade Chandra Kusuma (Majalah Ilmiah Bahari Jogja, 2020)
Competence in the form of the ability of prospective seamen, especially the crew face to face in the berthing process given to the Stimaryo cadets majoring in Nautical Studies in learning Maritime Skills so that they can easily adapt and can play a role in the bow during the ship leaning process. The main research objective in this study is that prospective seamen from Stimaryo especially the Nautika study majors in assisting learning in the form of role play can easily understand the material and know the attitudes that must be possessed and good skills in leading orders from platforms and cooperation with advance deck ABK groups. The research method used is descriptive research with the aim of making systematic, factual and accurate descriptions of the facts. The ability of prospective sailors leadership with role play learning models reaches values ​​above 75, so that their competencies are declared to be in accordance with the needs in the field. The roleplay learning model is able to form competencies through coordination as a communicator and communicant as well as a predetermined time.